Pengaruh Program UNNES PRIGEL pada Kesiapan Kerja Mahasiswa Pendidikan Teknik Otomotif Universitas Negeri Semarang - Yazid, Yazid; Budiman, Febrian Arif; Naryanto, Rizqi Fitri; Baihaqi, Setyo Bhahak Fendi (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2025)
Universities have an important role in preparing graduates who are not only intellectually superior but also have adequate work readiness. However, many students still have difficulty in developing skills due to limited practical experience. To answer this challenge, Semarang State University (UNNES) implemented the Merdeka Belajar Kampus Merdeka (MBKM) program through the UNNES PRIGEL (Graduate Generation Integrative Practice) flagship program. PRIGEL is an abbreviation of principles that have philosophical meanings, namely Passionate, Receptive, Innovative, Goal-Oriented, Embrace, and Leading-Edge. This program aims to encourage the development of students' potential, creativity, and independence through experiential learning in the field. This study aims to determine the effect of the UNNES PRIGEL program on the work readiness of students in the Automotive Engineering Education Study Program. The study uses a quantitative approach with an ex post facto type. The research instrument used was a questionnaire arranged in the form of closed questions using a Likert scale as the measurement method. The data analysis technique used was simple linear regression. The research sample consisted of 79 students taken using purposive sampling technique, namely all students who had participated in the UNNES PRIGEL program. The results of the study showed that the UNNES PRIGEL program had a positive effect on students' work readiness with a contribution of 61.1%. This finding confirms the importance of practice-based learning programs in improving the work readiness of higher education graduates.